WORKPLACE BULLYING AND PHYSICAL HEALTH OF TEACHERS WORKING IN HIGHER EDUCATION INSTITUTES - Anjum, Ambreen; Muazzam, Amina (Journal of Postgraduate Medical Institute, 2019)
Objective: To explore the relationship between workplace bullying and physical strains among teachers of higher education institutes. Methodology: In this cross-sectional study, a sample of 400 teachers was collected using non-probability purposive sampling from seven public sector universities of Lahore. The assessment was completed using standardized tools; Workplace Bullying Scale and Physical Strains Scale with demographic information sheet. Researcher collected the data from February 2017 to August 2017. Analysis was performed using SPSS version 23.0. Results: Out of 526 teachers, 200 male (50%) and 200 female (50%) teachers completed the survey. Mean age of sample was 34 ±8.0 years. Forty two percent of teachers reported experiences of workplace bulling. Workplace bullying (both person-related and work-related) was found to be a significant positive predictor and collectively account for 28% of the variance in physical strains. Females teachers had more exposure of bullying (66%) and significantly higher levels of physical strains as compared to male teachers (p =0.000). Conclusion: Large numbers of teachers are facing workplace bullying problem that needs to be addressed to improve their psychological and physical health.